What Book of Esther Did Josephus Read?: A Special Focus on the Old Latin - Candido, Dionisio (TC, 2024)
The biblical sources of Flavius Josephus’s Jewish Antiquities are still uncertain. Literary investigations have shown Josephus’s freedom in paraphrasing biblical accounts and omitting or adding sections, according to his own purposes. From a textual-critical point of view, the case of the Jewish Antiquities’s section on the book of Esther (11.184–296) is particularly complicated, since it is attested in three main variant editions: the Masoretic Text, the Old Greek, and the Alpha Text. This article will first offer an investigation of the readings that can be traced back to these three versions. It will also show how the Jewish Antiquities made different use of these versions in quantitative and qualitative terms. Second, the paper presents the alignments between the Jewish Antiquities and the Old Latin. The article will not only analyze the value of the alignments that have already been identified but also point to some new ones. The analysis provides a clearer view of the biblical sources Josephus employed in his rewrite of Esther.